Mental Disorders Among Healthcare Students Attending a Large University Hospital in Milan, Italy - Mendola, Marco; Masi, Francesco; Castiglione, Raimondo; Soriano, Antonio; Zazou, Safi; Tonelli, Fabio; Carrer, Paolo (La Medicina del Lavoro, 2024)
Background: The high incidence rates, treatment difficulties, and tendency to become chronic, which subsequently affects personal and occupational functioning, make mental health disorders among the most important public health concerns. In this context, healthcare university students (HS) appear to be more vulnerable to psychological distress than others. Objective: Investigate the prevalence of diagnosed mental illness among different groups of HS to detect students who may be psychologically vulnerable and determine whether the implementation of support interventions is necessary. Methods: All HS who had a clinical examination performed by an occupational physician at our occupational health unit between 2021 and 2022 were included in our case series. Data were collected and analyzed as part of the occupational physicians’ health surveillance program. Results: out of 679 HS (507 females, 172 males, aged 22.2±3.9 mean±s.d) undergone clinical examination at our Occupational Health Unit, 36 (5.3%) reported a diagnosed psychiatric illness, and 20 were receiving pharmacological therapy at the time of the visit. A higher prevalence of psychological disorders has been highlighted in females (6.1% vs 2.9% in males) and students of the mental health sector (11.1%) when compared with others. A fit-to-work judgment with prescription was necessary for 16.7% of students with mental diseases. The presence of psychiatric disorders was associated with underweight (27.8%) and higher smoking habit (44.4%). Conclusions: These results underline the necessity of improving the current health surveillance protocols, which should also evaluate students’ psychological fragility and implement effective intervention strategies to promote their health and wellbeing.